The Impact of the Tax Amendment on Salaries and Wages According to Article 09 of the Complementary Finance Law 2020. - عبد الرحيم نادية (Finance and Business Economies Review, 2021)
The study aims to analyze the impact of the amendments introduced by Article 09 of the complementary Finance Law 2020 on salaries and wages which are affected by. So, it turns out that the exemptions and reductions approved didn’t have the desired effect. It was very weak and didn’t lead to improving the level of concerned income